2007
DOI: 10.1002/bit.21344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture medium supplementation of tobacco NT1 cell suspension cultures on the N‐glycosylation of human secreted alkaline phosphatase

Abstract: We report for the first time that culture conditions, specifically culture medium supplementation with nucleotide-sugar precursors, can alter significantly the N-linked glycosylation of a recombinant protein in plant cell culture. Human secreted alkaline phosphatase produced in tobacco NT1 cell suspension cultures was used as a model system. Plant cell cultures were supplemented with ammonia (30 mM), galactose (1 mM) and glucosamine (10 mM) to improve the extent of N-linked glycosylation. The highest levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…In addition, it is reported that change of the ammonium concentration during the culture affects the amount of Gal and GlcNAc residues in CHO cells [43]. In plants, glycosylation is also altered by supplementing glucosamine and ammonia into the culture medium [44]. Further study of the increases in galactosylated glycans is required.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it is reported that change of the ammonium concentration during the culture affects the amount of Gal and GlcNAc residues in CHO cells [43]. In plants, glycosylation is also altered by supplementing glucosamine and ammonia into the culture medium [44]. Further study of the increases in galactosylated glycans is required.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, if these plant-specific glycans are present in an injected pharmaceutical product, the glycoprotein could trigger immunological response, or at least, result in a short circulation half-life. N -glycans of proteins produced from mammals are often terminated in β(1,4)-galactose and sialic acid; sialic acid is particularly important as it typically increases the circulation half-life of proteins [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…, 2001; Joosten and Shuler, 2003; Yoon et al. , 2004; Becerra‐Arteaga and Shuler, 2007). Moreover, high‐mannose type N ‐glycans were detected only in intracellular glycoproteins in rice suspension‐cultured cells (Maeda and Kimura, 2006), suggesting that the high‐mannose type glycans exist only on the rice intracellular glycoproteins.…”
Section: Discussionmentioning
confidence: 99%